Counseling Interventions for Suicide Prevention Among Youth in the United States: A Comprehensive Review of Psychosocial Risk Factors - Muhamad Solih (Asesment : Journal Of Counseling Guidance, 2025)
Background: Suicide remains the second leading cause of death among youth aged 10-24 years in the United States, with rates continuing to rise despite prevention efforts. Understanding current counseling intervention practices and factors associated with treatment effectiveness is critical for improving suicide prevention outcomes among this vulnerable population.Objective: This study examined counseling interventions for youth suicide prevention, identified psychosocial risk factors prioritized by mental health professionals, and determined factors associated with treatment effectiveness.Method: A quantitative cross-sectional survey was administered to 364 licensed mental health professionals across the United States. Data were collected on intervention approaches, psychosocial risk factor assessment practices, protective factors emphasis, treatment outcomes, counselor characteristics, and barriers to effective intervention. Hierarchical multiple regression and correlational analyses were conducted to identify predictors of treatment effectiveness.Findings and Implications: Cognitive-Behavioral Therapy and Dialectical Behavior Therapy were most frequently utilized, with DBT demonstrating superior effectiveness. Specialized training, protective factors emphasis, and barrier severity emerged as significant predictors of treatment effectiveness, explaining 47% of outcome variance. Results inform training programs, organizational practices, and policy reforms needed to enhance suicide prevention services.Conclusion: Effective youth suicide prevention requires evidence-based clinical practices, specialized counselor training, and systemic reforms addressing organizational and policy barriers to quality care delivery.